World Economic Outlook : Interim Assessment, December 1997. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
The economic and financial crisis that erupted in southeast Asia in July 1997 had continued to deepen and broaden as of December, and spillover effects from investor deteriorating confidence in emerging market economies were being felt throughout the global financial system. This special Interim Assessment of the World Economic Outlook revises regional and global economic projections made by the IMF staff, as published in the October 1997 issue, in light of the crisis; charts the buildup to the crisis and its onset and evolution; assesses effects on the advanced economies and on private financing for developing countries; and raises policy issues that the crisis has posed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Financial Markets; International Investment; Long-Term Capital Movements